2016
DOI: 10.3389/fmars.2016.00082
|View full text |Cite
|
Sign up to set email alerts
|

The Ferrojan Horse Hypothesis: Iron-Virus Interactions in the Ocean

Abstract: Iron is an essential nutrient and the sub-nanomolar concentrations of iron in open ocean surface waters are often insufficient to support optimal biological activity. More than 99.9% of dissolved iron in these waters is bound to organic ligands, yet determining the identity of these ligands in seawater remains a major challenge. Among the potential dissolved organic ligands in the colloidal fraction captured between a 0.02 and a 0.2 µm filter persists an extremely abundant biological candidate: viruses, most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 115 publications
(164 reference statements)
1
45
0
2
Order By: Relevance
“…This larger biomass is believed to be a liability, especially during bloom conditions, when they are preferentially preyed upon by eukaryotic protists and subject to viral lysis Yooseph et al, 2010). The interplay between addition of iron from dust deposition, bacterial iron uptake and viral infection is interesting in light of the recent proposed Ferrojan Hypothesis (Bonnain et al, 2016). This hypothesis suggests that viruses can adsorb free iron and then utilize bacterial iron-uptake receptors for infection in the manner of a Trojan Horse.…”
Section: Discussionmentioning
confidence: 99%
“…This larger biomass is believed to be a liability, especially during bloom conditions, when they are preferentially preyed upon by eukaryotic protists and subject to viral lysis Yooseph et al, 2010). The interplay between addition of iron from dust deposition, bacterial iron uptake and viral infection is interesting in light of the recent proposed Ferrojan Hypothesis (Bonnain et al, 2016). This hypothesis suggests that viruses can adsorb free iron and then utilize bacterial iron-uptake receptors for infection in the manner of a Trojan Horse.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that polysaccharides, EPS as well as viruses could represent a significant pool of colloidal iron binding ligands (Benner, 2011;Hassler et al, 2011a;Bonnain et al, 2016). Indeed, iron associated with the tails of phages might mimic Fesiderophore complexes thus providing an efficient way to infect heterotrophic bacteria (Bonnain et al, 2016).…”
Section: A Putative Role For Exopolymeric Substances In Size Distribumentioning
confidence: 99%
“…For example, non-marine tailed bacteriophages have been found to contain iron ions in the tail proteins that can utilize the siderophore-bound iron receptors on the host cell membrane for attachment of the phage and subsequent infection of the bacterial host (Bartual et al, 2010). It is likely that similar interactions also exists for marine bacteriophages (Bonnain et al, 2016). Still open questions are whether such phages will obtain fewer iron ions in their tail under Fe-deprivation, and if this will negatively affect their infectivity.…”
Section: Viral Infection Characteristicsmentioning
confidence: 99%
“…Still open questions are whether such phages will obtain fewer iron ions in their tail under Fe-deprivation, and if this will negatively affect their infectivity. Furthermore, the recently proposed "Ferrojan Horse Hypothesis" by Bonnain et al (2016) posits that introduction of phageattached Fe may aid the host. More study is needed to test this theory and its potential interference with siderophore-specific uptake mechanisms and effect on Fe cycling.…”
Section: Viral Infection Characteristicsmentioning
confidence: 99%